Autoimmune disease preceding amyotrophic lateral sclerosis: an epidemiologic study. - Turner, M; Goldacre, R; Ramagopalan, S; Talbot, K; Goldacre, M (2013)
OBJECTIVE: To study whether the risk of amyotrophic lateral sclerosis (ALS) is increased in people with prior autoimmune disease. METHODS: An all-England hospital record-linkage dataset spanning 1999-2011 was used. Cohorts were constructed of people with each of a range of autoimmune diseases; the incidence of ALS in each disease cohort was compared with the incidence of ALS in a cohort of individuals without prior admission for the autoimmune disease. RESULTS: There were significantly more cases than expected of ALS associated with a prior diagnosis of asthma, celiac disease, younger-onset diabetes (younger than 30 years), multiple sclerosis, myasthenia gravis, myxedema, polymyositis, Sjögren syndrome, systemic lupus erythematosus, and ulcerative colitis. CONCLUSIONS: Autoimmune disease associations with ALS raise the possibility of shared genetic or environmental risk factors.